2014
DOI: 10.1182/blood-2014-01-545020
|View full text |Cite
|
Sign up to set email alerts
|

A highly compact epitope-based marker/suicide gene for easier and safer T-cell therapy

Abstract: Key Points Marker genes enable detection and selection of T cells, whereas suicide genes enable selective destruction of T cells in case of toxicity. RQR8 is a 136-amino-acid epitope-based marker/suicide gene that enables clinical selection, cell tracking, and deletion in case of toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
302
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 329 publications
(304 citation statements)
references
References 33 publications
2
302
0
Order By: Relevance
“…In previous studies, we have shown that RQR8-transduced cells are effectively depleted from mice with rituximab. 32 Others have shown that elimination of redirected T cells based on suicide genes may protect against side effects in patients. 44 The TCRs studied herein were derived from CD4 C Th cells, but are still functional in CD8…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous studies, we have shown that RQR8-transduced cells are effectively depleted from mice with rituximab. 32 Others have shown that elimination of redirected T cells based on suicide genes may protect against side effects in patients. 44 The TCRs studied herein were derived from CD4 C Th cells, but are still functional in CD8…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that administration of the anti-CD20 antibody rituximab mediates effective deletion of RQR8-exopressing T cells in vitro and in vivo. 32 …”
Section: Selection Of Two Dp-4 Restricted T-cell Clones For Molecularmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, the truncated EGFR, co-expressed with the CAR by the same T cell, can be targeted by the antibody cetuximab which efficiently eliminates those marked cells [117]. Efforts are also being undertaken to coexpress the targetable epitope within the extracellular part of the CAR, thereby making the CAR itself a target of a depleting antibody [118]. An anti-idiotypic antibody directed against the scFv of the CAR itself may be used for depleting CAR T cells as well [119].…”
Section: (V) Car T Cell Eliminationmentioning
confidence: 99%